Encourage The Advance Of Artificial Intellegent In Replacement The Position Of Civil Servant Apparatus During Pandemic To Reduce The Nepotism In Indonesia’s Bureaucracy - Yuwan Zaghlul Ismail (ConCEPt - Conference on Community Engagement Project, 2021)
Artificial Intelligent is intelligent demonstrated by machines that’s specifically have some similarities with human intelligences, Indonesia reported have the ARTIFICIAL intelligent ROBOT, the intention of Mr. President to replace the ASN with Artificial Intelligent in the government will soon be realistic, Indonesia actually now have a great Artificial intelligent robot, but the utilization of AI robot in Indonesia still very lack, it’s still need the transition era for this in replacement. The use of AI robot still rise so many questions in law, on how the position of AI regulated in Indonesian Law, as we know that its robot intelligently work like human that they can understand and can respond like human, but what become the question law or provision drafting is about the emergence situation, the robot still cannot detect whether it’s it rushing situation or not, the drafting of the law in the AI itself always can be related with cyber law, but in my own understanding even though the draft of law in cyber law are enough to regulate about Artificial intelligent itself but the law need to ruled more about the Artificial intelligent, there can be any error, the question arise that who should we blame with those artificial intelligent commit error during the process of bureaucracy then affect so many system in another sector, so the law should draft more about that in order to prevent the error that can be caused by the AI itself, In order to achieve bureaucracy 4.0, the government have to work seriously without involving the personal interest in nit, bureaucracy 4.0 has four indicators. These indicators are service acceleration, service efficiency, service accuracy, work flexibility, and social impact. With the flexibility of ASN working time, work does not have to be done in the office. In the future, some jobs can be done via smartphones, which of course will be more efficient and shorten the flow of bureaucracy. It is in this context that explained about ASN that can work from home which is the attention of the mass media